Menguatkan Fondasi Keluarga: Peran Pemerintah Daerah DIY dalam Meningkatkan Ketahanan Keluarga - Kaamiliaa Dewi; Isnaini Muallidin (Nakhoda: Jurnal Ilmu Pemerintahan, 2025)
This study aims to analyze the role of the Yogyakarta Special Region (DIY) Regional Government in strengthening family resilience, with a focus on the implementation of policies and programs designed to support the family as the fundamental unit of society. The urgency of this research lies in the increasing social and economic challenges faced by DIY families, such as high poverty rates, domestic violence, divorce, and limited access to basic services, which collectively threaten family stability and community prosperity. Using a qualitative descriptive method, this research collects and analyzes secondary data from scientific journals, government reports, and policy documents published between 2015–2025. Data analysis was conducted through literature review and thematic mapping using VOS Viewer to identify key themes and group priorities. The results show that the DIY Regional Government plays a strategic role as regulator, dynamisator, facilitator, and catalyst in supporting family resilience through programs such as prenatal education, family economic empowerment, social assistance, and cross-sector coordination. However, challenges such as budget constraints, lack of inter-institutional synergy, and low community participation remain obstacles. The study concluded that strengthening family resilience in DIY requires an integrated and collaborative approach involving local governments, NGOs, the private sector, and the community, with an emphasis on education, economic stability, social support, and women's empowerment as key pillars of sustainable family development